Generation of Foxp3+CD25− Regulatory T-Cell Precursors Requires c-Rel and IκBNS - Schuster, Marc; Plaza-Sirvent, Carlos; Visekruna, Alexander; Huehn, Jochen; Schmitz, Ingo (Frontiers in Immunology, 2019)
Next to the classical developmental route, in which first CD25 and subsequently Foxp3 are induced to generate thymic regulatory T (Treg) cells, an alternative route has been described. This alternative route is characterized by reciprocal induction of Foxp3 and CD25, with CD25 induction being required to rescue developing Treg cells from Foxp3-induced apoptosis. NF-kB has been demonstrated to be crucial for the development of thymic Treg cells via the classical route. However, its impact on the alternative route is poorly characterized. Using single and double deficient mice for key regulators of the classical route, c-Rel and IkBNS, we here demonstrate that NF-kB is essential for the generation of alternative CD25-Foxp3+ precursors, as well. Thus, c-Rel and IkBNS govern both routes of thymic Treg cell development.